2013
DOI: 10.1039/c2ob26705e
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-8 agonistic activities in C2, C4, and C8 modified thiazolo[4,5-c]quinolines

Abstract: Toll-like receptor (TLR)-8 agonists typified by the 2-alkylthiazolo[4,5-c]quinolin-4-amine (CL075) chemotype are uniquely potent in activating adaptive immune responses by inducing robust production of T helper 1-polarizing cytokines, suggesting that TLR8-active compounds could be promising candidate vaccine adjuvants, especially for neonatal vaccines. Alkylthiazoloquinolines with methyl, ethyl, propyl and butyl groups at C2 displayed comparable TLR8-agonistic potencies; activity diminished precipitously in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 56 publications
0
79
0
Order By: Relevance
“…The title compound was prepared according to the procedure described by H. Kokatla et al. 28 Compound 34 (200 mg, 0.98 mmol) was dissolved in a mixture of anhydrous DCM/anhydrous DMF: 10/1 (Volume: 22ml) and stirred at room temperature for 5 min. …”
Section: N1-(35-dimethylphenyl)-n2-(4-hydroxy-6-methoxy-2-methylquinmentioning
confidence: 99%
See 1 more Smart Citation
“…The title compound was prepared according to the procedure described by H. Kokatla et al. 28 Compound 34 (200 mg, 0.98 mmol) was dissolved in a mixture of anhydrous DCM/anhydrous DMF: 10/1 (Volume: 22ml) and stirred at room temperature for 5 min. …”
Section: N1-(35-dimethylphenyl)-n2-(4-hydroxy-6-methoxy-2-methylquinmentioning
confidence: 99%
“…In addition, this site was also suspected of being a contributor to the fast (oxidative) metabolism observed for the hit compounds. In this initial proof-of-concept compound set, the substituent choice was limited to small aliphatic groups (methyl and ethyl) and a phenyl ring (27)(28)(29)(30) Next, four conformationally constrained analogues were prepared (31, 32, 37 and 40). In compounds 31, 32 and 37 conformational locking was accomplished by an additional ring closure, while in the case of analogue 40 the oxalyl diamide fragment was expected to rigidify the linker region into a constrained conformation.…”
Section: Introductionmentioning
confidence: 99%
“…1), and thiazoloquinolines such as CL075 [13] ( 1 , Fig. 1), and the 2-aminobenzazepine VTX-2337 [14] display mixed TLR7/TLR8-agonism.…”
mentioning
confidence: 99%
“…In addition, several SAR studies indicated that the TLR8 activity was sensible to the length of C2-alkyl chain (8,9,11) and thus the hydrophobic centroid (H 4 ) of the C2-propyl of CL075 accounts different from the hydrophobic centroid (H 1 ) of other ligands were treated as two features. Usually, the effective pharmacophore models have 3-5 features; thus, we have limited our pharmacophore models to have 3-5 features only.…”
Section: Assessment Of Multiple Vs Strategiesmentioning
confidence: 99%
“…To date, several synthetic small molecules have been identified as agonists of TLR8, leading to detailed structureactivity relationship (SAR) studies on these chemotypes including furo [2,3-c]pyridines, furo [2,3-c]quinolines, thiazolo [4,5-c]quinolines, 3-R-quinoline-2-amine, and C7-methoxycarbonylimidazoquines (8)(9)(10)(11). As yet, current experimental studies on TLR8 agonists are focused on limited chemotypes, and the information of TLR8 agonist binding has not been fully exploited.…”
mentioning
confidence: 99%